Microbial phytase and zinc sulphate supplementation on performance and tissue zinc accumulation in broiler chicks - Dalkilic, Bestami; Azman, M.A.M.; Ciftci, Mehmet; Telo, Selda (My University, 2009)
The aim of this study was to determine the effects of supplementation of microbial phytase (Natuphos 500, Kartal Kimya - Turkey, 500 000 Units (FTU)/kg) to diets containing supplemental zinc and copper on performance and tissue zinc accumulation of broiler chicks. Final body weight, daily weight gain, feed consumption and feed conversion ratio were not affected (P<0.05) by the treatments. Phytase supplementation had not affected the percentage of tibia ash, tibia and liver Zn concentration. Copper concentration in tibia and liver was depressed (P<0.01) due to phytase supplementation.